Solving smart city revitalisation problems with geoparticipation process and fuzzy methods - Olszewski, Robert; Trojanowska, Hanna; Turek, Agnieszka; Kietlinska, Bogna (2017 13th International Conference on Natural Computation, Fuzzy Systems and Knowledge Discovery (ICNC FSKD), 2017)
The paper presents an exceptionally simple method that allows a researcher to find out the interpretation of the complicated revitalization processes on the bases of the collected data. It employs spatial data mining and fuzzy inference system. Thanks to building the FIS knowledge base and selecting the fuzzy rules, it is possible to point out the important factors that influence the process that is being the subject of the research. In this paper this is the dialogue between Polish local governments and their residents to solve the problem of urban revitalization in the context of smart city creation.